The Prevalence of Irritable Bowel Syndrome Among Chinese University Students: A Systematic Review and Meta-Analysis - Yang, Weixin; Yang, Xiao; Cai, Xianghao; Zhou, Zhuoren; Yao, Huan; Song, Xingrong; Zhao, Tianyun; Xiong, Peng (Frontiers in Public Health, 2022)
Background: Irritable bowel syndrome (IBS) has become a common public health issue among university students, impairing their physical and mental health. This meta-analysis aimed to examine the pooled prevalence of IBS and its associated factors among Chinese university students. Methods: Databases of PubMed, EMBASE, MEDLINE (via EBSCO), CINAHL (via EBSCO), Wan Fang, CNKI and Weipu (via VIP) were systematically searched from inception date to May 31, 2021. Meta-analysis was performed using random-effects models. Meta-regression and subgroup analysis were used to detect the potential source of heterogeneity. Key Results: A total of twenty-two cross-sectional studies (14 were in Chinese and 8 were in English) with 33,166 Chinese university students were included. The pooled prevalence of IBS was estimated as 11.89% (95% CI= 8.06%, 16.35%). The prevalence was 10.50% (95% CI=6.80%, 15.87%) in Rome II criteria, 12.00% (95% CI=8.23%, 17.17%) in Rome III criteria, and 3.66% (95% CI=2.01%, 6.60%) in Rome IV criteria. The highest prevalence of IBS was 17.66% (95% CI=7.37%, 36.64%) in North China, and the lowest was 3.18% (95% CI=1.28%, 7.68%) in South China. Subgroup analyses indicated that gender, major, anxiety and depression symptoms, drinking and smoking behaviors were significantly associated with the prevalence of IBS. Meta-regression analyses suggested that region influenced prevalence estimates for IBS. Conclusions & Inferences: This meta-analysis illustrated that IBS is very common in Chinese university students. Regular screening, effective prevention, and appropriate treatments should be implemented to reduce the risk of IBS in this population. More future studies should be conducted in Northeastern and Southwestern parts of China. Keywords: Irritable Bowel Syndrome; Prevalence; Associated Factors; Chinese University Students; Meta-Analysis